Virological blips and predictors of post treatment viral control after stopping ART started in primary HIV infection - Fidler, S; Olson, A; Bucher, H; Fox, J; Thornhill, J; Morrison, C; Muga, R; Phillips, A; Frater, J; Porter, K (Lippincott, Williams & Wilkins, 2017)
Background: Few individuals commencing antiretroviral therapy (ART) in primary HIV infection (PHI) maintain undetectable viremia after treatment cessation. Associated factors remain unclear given the importance of the phenomenon to cure research. Methods: Using CASCADE data of seroconverters starting ART in PHI (≤6 months from seroconversion), we estimated proportions experiencing viral blips (>400 copies followed by <400 copies HIVRNA/ mL without alteration of regimen) while on ART. We used Cox models to examine the association between time from ART stop to loss of control (2 consecutive measurements >1000 copies per milliliter) and magnitude and frequency of blips while on ART, time from seroconversion to ART, time on ART, adjusting for mean number of HIV-RNA measurements/year while on ART, and other confounders. Results: Seven hundred seventy-eight seroconverters started ART in PHI with ≥3 HIV-RNA measurements. Median interquartile range (IQR) ART duration was 16.2 (8.0-35.9) months, within which we observed 13% with ≥1 blip. Of 228 who stopped ART, 119 rebounded; time to loss of control was associated with longer interval between seroconversion and ART initiation [hazard ratio (HR) = 1.16 per month; 1.04, 1.28], and blips while on ART (HR = 1.71 per blip; 95% confidence interval = 0.94 to 3.10). Longer time on ART (HR = 0.84 per additional month; 0.76, 0.92) was associated with lower risk of losing control. Of 228 stopping ART, 22 (10%) maintained post treatment control (PTC), ie, HIV-RNA <50 copies per milliliter ≥24 months after ART cessation. Conclusion: HIV viral blips on therapy are associated with subsequent viral rebound on stopping ART among individuals treated in PHI. Longer duration on ART is associated with a greater chance of PTC.